Pengaruh Model Kooperatif Student Teams Achievment Divisions Terhadap Motivasi Siswa Dalam Pembelelajaran Pencak Silat MTS Al-Hasanah - Dendy Firmansyah; Akhmad Dimyati; Siswanto Siswanto (Ilmu Olahraga, 2023)
Motivation is a person's desire to achieve something at the instigation of oneself and others. Motivation is needed in carrying out various activities, especially in the learning process. This study aims to determine, analyze, and identify the effect of the Cooperative Student Teams Achievement Divisions model on the learning motivation of MTS Al-Hasanah students. The method in this research is experimental, where the research sample is class VII A students with a total of 27 students and class VII B as many as 21 students. This research was conducted using the STAD cooperative learning model for class VII A and the conventional learning model for class VII B, sampling using purposive sampling and the research design using two groups of pre-test-post-test. For the research instrument, using skills tests and questionnaires, in collecting data using a basic skill test of pencak silat through a pre-test-post test, then a motivational questionnaire is given to measure the extent of students' motivation in participating in learning. The results of this study obtained a significance value of 0.000 <0.005 which means that there is an effect of implementing the STAD type cooperative model with a percentage of 27.93%. Where there is a change and increase in students' learning motivation in learning pencak silat at MTS Al-Hasanah.